On the Amount of Information Resulting from Empirical and Theoretical Knowledge - Vajda, Igor; Zvarova, Jana; Vesely, Arnoˇst (Revista Matemática Complutense, 2005)
We present a mathematical model allowing formally define the concepts of empirical and theoretical knowledge. The model consists of a finite set P of predicatesand a probability space (, S, P) over a finite set called ontology which consists of objects ! for which the predicates _ 2 P are either valid (_(!) = 1) or not valid (_(!) = 0). Since this is a first step in this area, our approach is as simple as possible, but still nontrivial, as it is demonstrated by examples. More realistic approach would be more complicated, based on a fuzzy logic where the predicates _ 2 P are valid on the objects ! 2 to some degree (0 _ _(!) _ 1). We use the classical information divergence to introduce the amount of information in empirical and theoretical knowledge. By an example is demonstrated that information in theoretical knowledge is an extension of the “sematic information” introduced formerly by Bar Hillel and Carnap as an alternative to the information of Shannon.